Rat melanin concentrating hormone does not modify the release of CRH-41 from rat hypothalamus or ACTH from the anterior pituitary in vitro. - Navarra, P; Tsagarakis, S; Coy, D; Rees, L; Besser, G; Grossman, AB (1990)
It has been suggested that melanin concentrating hormone (MCH) possesses potent corticotrophin (ACTH) inhibitory activity, on the basis of the inhibitory effects displayed by salmon MCH on ACTH release from either trout or rat isolated pituitary fragments. Recently, rat MCH has been characterised, and this prompted us to investigate the putative inhibitory activity of synthetic rat MCH on basal and stimulated ACTH secretion from freshly-dispersed rat pituitary cells or incubated rat pituitary fragments, as well on KCl (28 mmol/l) or noradrenaline-evoked release of corticotrophin releasing hormone-41 (CRH-41) from rat hypothalamic explants in vitro. There were no effects of rat MCH on either CRH-41 or ACTH release in vitro.